Offshore wind energy as an emergent ocean infrastructure in India: Mapping of the social and environmental impacts - Gopal K. Sarangi (Asian Development Bank Institute (ADBI), 2022)
Offshore wind energy holds promising potential as an alternative source of energy for a country like India, which continues to be land deprived and faces increasing difficulty in acquiring land for energy. While some scholarly efforts have focused on the Indian context, there is a dearth of studies on the associated environmental and social challenges of such infrastructure deployment. The paper conducts a detailed assessment of the policy and institutional mechanisms governing the offshore wind energy in the country and identifies the possible environmental and social impacts of such projects on the marine environment and livelihood of fishing communities in India. It employs qualitative research approaches and various types of secondary information and data. The policy and institutional framework assessment reveals that, despite the creation of the required mechanism, significant gaps exist in the knowledge of such projects' possible impacts through these policies and regulations. Impact mapping shows that offshore wind projects could adversely affect the marine eco-system and marine biodiversity to varying degrees over their entire life. The impacts occurring during the construction and operation phases of the project cycle will be significant. Policy suggestions show that preparatory measures are necessary before the implementation of such projects.
Keywords: E2; O13; O18; Q42; 330; offshore wind energy; environment; livelihood; India